Structure, Transport, and Seasonality of the Atlantic Water Boundary Current North of Svalbard: Results From a Yearlong Mooring Array. Issue 3 (14th March 2019) - Pérez‐Hernández, M. Dolores; Pickart, Robert S.; Torres, Daniel J.; Bahr, Frank; Sundfjord, Arild; Ingvaldsen, Randi; Renner, Angelika H. H.; Beszczynska‐Möller, Agnieska; von Appen, Wilken‐Jon; Pavlov, Vladimir
Abstract: The characteristics and seasonality of the Svalbard branch of the Atlantic Water (AW) boundary current in the Eurasian Basin are investigated using data from a six‐mooring array deployed near 30°E between September 2012 and September 2013. The instrument coverage extended to 1, 200‐m depth and approximately 50 km offshore of the shelf break, which laterally bracketed the flow. Averaged over the year, the transport of the current over this depth range was 3.96 ± 0.32 Sv (1 Sv = 10 6 m 3 /s). The transport within the AW layer was 2.08 ± 0.24 Sv. The current was typically subsurface intensified, and its dominant variability was associated with pulsing rather than meandering. From late summer to early winter the AW was warmest and saltiest, and its eastward transport was strongest (2.44 ± 0.12 Sv), while from midspring to midsummer the AW was coldest and freshest and its transport was weakest (1.10 ± 0.06 Sv). Deep mixed layers developed through the winter, extending to 400‐ to 500‐m depth in early spring until the pack ice encroached the area from the north shutting off the air‐sea buoyancy forcing. This vertical mixing modified a significant portion of the AW layer, suggesting that, as the ice cover continues to decrease in the southern Eurasian Basin, the AW will be more extensively transformed via local ventilation. Plain Language Summary: The Svalbard branch of the Atlantic Water (AW) flows eastward north of Svalbard carrying warm and salty waters along the slope of the western Eurasian Basin. Here we explore the characteristics and seasonality of the boundary current using data from a six‐mooring array deployed at 81.7°N, 30.6°E between September 2012 and September 2013. On average the current carries 3.96 ± 0.32 Sv (1 Sv = 10 6 m 3 /s) of which 2.08 ± 0.24 Sv is of AW. From late summer to early winter the AW was warmest and saltiest, and its eastward transport strongest, while from midspring to midsummer the AW was coldest and freshest and its transport weakest. In this region, the layer of AW is modified via convective overturning in winter. Key Points: The 2012‐2013 average volume transport of the Atlantic Water boundary current north of Svalbard is 2.08 ± 0.24 Sv The transport is maximum in late summer to early fall when the Atlantic Water is warmest and saltiest The Atlantic Water layer is ventilated locally via convective overturning in winter and early spring before ice is advected into the region